ldcf.net
当前位置:首页 >> 1.6—0.5x=2.7x+0.16 >>

1.6—0.5x=2.7x+0.16

2.7X-1.6 = 38.9X÷4.5 = 20(0.5+x)+x=9.8÷2 2(X+X+0.5)=9...3x-8=16 7(x-2)=2x+3 3x+9=270 12x=300-4x 7x+5.3=7.4 3x÷5...

=(1.5+4.8÷1.6x0.1)x2.7 =(1.5+3x0.1)x2.7 =1.8x2.7

(10-6.76)÷1.2] = 0.8 x(3.24÷1.2) = 0.8 x 2.7 = 2.16...6-1.6÷4= 6- 0.4 = 5.65.38+7.85-5.37= 13.23 - 5.37=7.86 7...

(1)x²-34x+288=0 (x-16)(x-18)=0 x=16 或 x=18 (2)0.5x²-0.1x+2.7=0 解:由判别式△=b²-4ac=(-0.1)²-4x0.5x2.7=-5.39

0.16÷(x-1又25分之24)=1又20分之7÷2.7 0.16÷(x-1又25分之24)=20分之27÷2.7 0.16÷(x-1又25分之24)=0.5 x-1又25分之24=0.16÷0.5 x-1又25分之24=0.32 x-1.96=0.32 x=0.32+1.96 x=2.28

(1)0.16÷(x?12425)=1720÷2.7, 0.16÷(x?12425)×12425x=12×12425x, 0.16=0.98x, 0.16÷0.98=0.98x÷0.98, x=849;(2)12:20%=214:(x+0.3),12×(x+0.3)=20%×214, 12x+320=920, 12x+320?320=920?320, 12x÷12=310÷12, x=35.

5.5x=1.1 解得 x=0.2

(1)16-x÷3=10 16-x÷3-10=10-10 6-x÷3+(x÷3)=0+x÷3 x÷3=6 x÷3×3=6×3 x=18;(2)5x+3(x-2)=15.6 5x+3x-6=15.6 8x-6=15.6 8x-6+6=15.6+6 8x=21.6 8x÷8=21.6÷8 x=2.7;(3)6x-48=5x+3 6x-48+48=5x+3+48 6x=5x+51 6x-5x=5x+51-5x x=51;(4)...

网站首页 | 网站地图
All rights reserved Powered by www.ldcf.net
copyright ©right 2010-2021。
内容来自网络,如有侵犯请联系客服。zhit325@qq.com